Communication Strategy in the Implementation of Waste Management Public Policy in the Tasikmalaya District - Hayati, Neni Nur; Wahyudin, Uud; Bajari, Atwar; Sjoraida, Diah Fatma (Jurnal Komunikasi, 2024)
The lack of public awareness of waste management seems to be a never-ending problem. Tasikmalaya Regency is one of the areas in West Java that has received much attention for being a regency surrounded by garbage around the main road. This article aims to determine the government's communication strategy in implementing public policies related to waste management in Tasikmalaya Regency. This research uses a constructivist paradigm with a descriptive qualitative approach through observation and in-depth interviews. The results show that the local government has made a strong commitment through Tasikmalaya District Regulation Number 3 Year 2022 on Waste Management to solve the waste problem in Tasikmalaya. However, in its implementation, there are communication barriers, both internally and externally, that cause policy implementation to be far from the predetermined target because the socialization of rules, including education to the community, is not massive and maximum so that the messages conveyed do not change people's behavior. This condition has profound implications for the lack of citizen participation in overcoming and minimizing waste piles. Weak law enforcement is a problem, especially for industrial plastic waste producers. Infrastructure issues, including facilities such as waste transportation fleets, waste disposal facilities, human resources, and budget limitations, are still arduous for local governments. Environmental communication is the key to two-way interaction between the government, community, and stakeholders.